FORCES AND DISPLACEMENTS DISTRIBUTION AFTER FEM ANALYSIS OF VIBRATORY WORKING TOOL - NELUS-EVELIN GHEORGHITA (Journal of Engineering Studies and Research)
The research status and the study of vibratory working tools used in tillage operations are discussed in this paper. At this moment, one of the most critical issues for the engineers and manufacturers is to achieve the highest efficiency with the least resources needed. Various studies by researchers on vibratory working tool styles and models have been taken into account. A study was then conducted to ascertain the advantages of vibratory equipment over rigid equipment. A finite element process study was also conducted on one active working tool to observe specific deformations and displacements. Draft forces ranging from 440 to 750 N were used in the study. According to prior studies, the angle of attack after the forces have been applied should not exceed 80 degrees.